Abatacept monotherapy compared with abatacept plus disease-modifying anti-rheumatic drugs in rheumatoid arthritis patients: data from the ORA registry. Issue 1 (December 2016) - Truchetet, Marie-Elise; Poursac, Nicolas; Barnetche, Thomas; Shipley, Emilie; Gottenberg, Jacques-Eric; Bannwarth, Bernard; Richez, Christophe; Schaeverbeke, Thierry
Abstract Background Retention rate, efficacy, and safety of abatacept (ABA) was compared between patients with rheumatoid arthritis receiving ABA as monotherapy to those in combination ABA + conventional synthetic DMARD (csDMARD). Methods The patients were obtained from the ORA registry. The retention rate was analysed in two ways: (1) therapeutic strategy retention, in which the addition of a csDMARD was considered to indicate failure of the monotherapy strategy; and (2) ABA retention, which was assessed by the discontinuation of ABA regardless of other treatment modifications. Efficacy and safety were compared between ABA initiated alone and ABA used in combination with a csDMARD. Results The retention rate at month 6 (M6) was evaluated in 569 patients. A significant difference was identified in the retention rate between the ABA monotherapy strategy and the ABA + csDMARD strategy (58.5 % [110/188] vs. 68 % [258/381], respectively, p  = 0.031). No significant difference was identified in the ABA retention rate initiated either as a monotherapy or in combination with csDMARDs (75 % [142/188] vs. 76 % [291/381], respectively, p  = 0.824). Data regarding ABA efficacy were available for 444 patients. There was no significant difference in the responder proportion after 6 months of treatment between ABA monotherapy and ABA + csDMARD treatment (60.2 % [88/146] vs. 60 % [179/298], respectively, p  = 0.967). Conclusions This "real-life" analysis, which is relevant for bedside practice, emphasised the satisfactory efficacy and safety of ABA used in monotherapy, which provides an acceptable alternative when csDMARDs are undesirable.